Two new Pleurothallidinae (Orchidaceae) from Southwestern Ecuador: Acianthera pustulata and Lepanthes marioi - Zambrano Romero, Bosco Javier; Solano, Rodolfo (Phytotaxa, 2019)
Acianthera pustulata and Lepanthes marioi are described and illustrated as new species. Both orchids belong to the Pleurothallidinae subtribe and were discovered in Southwestern Ecuador. Information concerning distribution, habitat, and phenology are provided for each species. Acianthera pustulata is compared with A. geminicaulina, from which it differs by its repent habit, pustulate sepals on abaxial surface, petals with a longitudinal callus, and a lip with a glenion. Meanwhile, L. marioi is very similar in form of their flowers with L. caudatisepala and differs from it by its greater habit, shorter and arching inflorescence, non apiculate petals with an elliptic callus along the mid-vein, and lip with a shortly oblong appendix, covered by a dense pubescens. Furthermore, Acianthera pustulata is also compared with two morphologically similar species, A. juxtaposita and A. lanceana; meanwhile L. marioi is compared with L. profusa, L. nanegalensis, L. repens, and L. rhombipetala.